2019
DOI: 10.3390/ijerph16173173
|View full text |Cite
|
Sign up to set email alerts
|

Physical Condition Factors that Predict a Better Quality of Life in Women with Fibromyalgia

Abstract: What physical qualities can predict the quality of life (QoL) in women with fibromyalgia (FM)? QoL is a very complex outcome affected by multiple comorbidities in people with fibromyalgia. This study aims to determine which physical qualities can predict the quality of life in women with FM. Also, a comparison between the physical qualities of women with FM and healthy counterparts was conducted. In total, 223 women participated in this cross-sectional study, 123 with FM, with ages ranging between 45 and 70 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 65 publications
0
19
0
3
Order By: Relevance
“…Of these, 345 were excluded for not meeting the inclusion criteria (reasons for their exclusion are showed in Figure 1 ). Finally, 19 studies [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] were included in the review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 345 were excluded for not meeting the inclusion criteria (reasons for their exclusion are showed in Figure 1 ). Finally, 19 studies [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…The methodological quality of the included studies assessed by the NOS ( Table 3 ) was medium (NOS mean quality of 4.21 ± 0.78 stars). Three studies [ 43 , 44 , 48 ] (16% of the total) were scored as low quality and 16 studies [ 38 , 39 , 40 , 41 , 42 , 45 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] (84% of all) were medium quality. A possible risk of selection and confounding bias was present due to the little information provided by the included studies of the characteristics of exposed and non-exposed (S1, S2, S3 and S4 items) and its comparability (C1).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding functional capacity, Carbonell-Baeza showed that multidisciplinary interventions alone might improve body flexibility in FMS patients [30]. Interestingly, previous case–control studies have been conducted, relating functional status and BMI to other psychological variables [37,38,39,40,41]. Sampere-Rubio et al reported that women with FM show a significantly lower QoL than their healthy counterparts, and the factors that predict their perceived QoL are functional capacity, muscular strength, postural maintenance, pain threshold, and anxiety [37].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous case–control studies have been conducted, relating functional status and BMI to other psychological variables [37,38,39,40,41]. Sampere-Rubio et al reported that women with FM show a significantly lower QoL than their healthy counterparts, and the factors that predict their perceived QoL are functional capacity, muscular strength, postural maintenance, pain threshold, and anxiety [37]. In this line, higher depression ranges were shown in women who suffered from FMS with respect to healthy controls, regardless of age distribution [39], and adolescents with FMS were found be more sensitive to pressure pain than their healthy peers [40].…”
Section: Discussionmentioning
confidence: 99%
“…En la población general, mayores niveles de fuerza muscular han demostrado estar relacionados con una disminución del riesgo de desarrollar enfermedad cardiovascular y de mortalidad prematura 6 . Concretamente, la fuerza de prensión manual (FPM), ha sido propuesta como un indicador de salud muy relevante en diferentes poblaciones: adultos mayores 7 , jóvenes 8 , mujeres con fibromialgia 9 , etc., permitiendo obtener información muy útil a través de una evaluación sencilla, rápida y de muy bajo coste.…”
Section: Introductionunclassified